2016
DOI: 10.1182/blood-2015-07-661371
|View full text |Cite
|
Sign up to set email alerts
|

Dicer1-mediated miRNA processing shapes the mRNA profile and function of murine platelets

Abstract: Human platelets contain microRNAs (miRNAs) and miRNA processing machinery, but their contribution to platelet function remains incompletely understood. Here, we show that murine megakaryocyte (MK)-specific knockdown of Dicer1, the ribonuclease that cleaves miRNA precursors into mature miRNAs, reduces the level of the majority of miRNAs in platelets. This leads to altered platelet messenger RNA (mRNA) expression profiles and mild thrombocytopenia. Fibrinogen receptor subunits Itga2b (αIIb) and Itgb3 (β3) mRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 50 publications
3
74
1
3
Order By: Relevance
“…29,38,[84][85][86] Through ribosome profiling, we show that much of this transcriptional complexity indeed shapes the platelet proteome through protein synthesis by platelet ribosomes. We combine our high-throughput RNA-Seq and ribosome profiling data with published mass spectrometry studies to present the first integrated view of platelet gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,38,[84][85][86] Through ribosome profiling, we show that much of this transcriptional complexity indeed shapes the platelet proteome through protein synthesis by platelet ribosomes. We combine our high-throughput RNA-Seq and ribosome profiling data with published mass spectrometry studies to present the first integrated view of platelet gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous specific examples of proteins synthesized by platelets have been described, [32][33][34][35][36] and an active microRNA pathway has been studied 26,27,29,37,38 and implicated in regulating mRNA decay and translation in platelets. 29 Because it is technically difficult to study platelet populations of different ages in vivo, 39 RNA-Seq studies have reported on an "ensemble" average of platelet transcripts that are influenced by the underlying age distribution of circulating platelets at the time of sample collection. Given the documented clearance of RNA by platelets during the first several days of circulation, 3,10,12 it seems likely that platelet protein synthesis primarily occurs within a few days of release from the MK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study by Rowley et al [32], however, showed that murine megakaryocyte-specific knockdown of Dicer1, the ribonuclease that cleaves miRNA precursors into mature miRNAs, reduced the level of the majority of microRNAs in platelets, altered platelet mRNA expression profiles and induced mild thrombocytopenia. Dicer1 deletion resulted in increased surface expression of integrins alphaIIb and beta3, and enhanced platelet binding to fibrinogen in vivo and in vitro.…”
Section: A Role For Micrornas In Platelet Function?mentioning
confidence: 99%
“…A critical transcription factor for megakaryocyte development and thrombopoiesis is RUNX1, which has been shown to repress the erythroid gene expression program, thus facilitating megakaryocyte differentiation 22. Furthermore, RUNX1 regulates cytoskeletal genes such as MYH9 and MYH10 and plays a role in megakaryocyte ploidy and proplatelet formation 23, 24, 25. ETV6, a member of the ETS transcription factor family, is required for late megakaryopoiesis and hematopoietic stem cell survival 26.…”
Section: Genetic Regulation Of Normal Megakaryopoiesismentioning
confidence: 99%